2014
DOI: 10.1016/j.ultsonch.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-based treatment approaches for intrinsic viscosity reduction of polyvinyl pyrrolidone (PVP)

Abstract: The present work deals with achieving viscosity reduction in polymer solutions using ultrasound-based treatment approaches. Use of simple additives such as salts, or surfactants and introduction of air at varying flow rates as process intensifying parameters have been investigated for enhancing the degradation of polyvinyl pyrrolidone (PVP) using ultrasonic irradiation. Sonication is carried out using an ultrasonic horn at 36 kHz frequency at an optimized concentration (1%) of the polymer. The degradation beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Kinetic analysis revealed that for the change in power dissipation from 8 W to 32 W, the rate constant was found to increase from 0.010 min À1 to 0.018 min À1 . Pawar et al [19] reported a similar trend for the ultraviolet induced degradation of aqueous solution of polyvinyl pyrrolidone (PVP) investigated over the power dissipation range of 5 W to 11 W and it was established that the kinetic rate constant increased from 3.1 Â10 À2 min À1 to 7.3 Â 10 À2 min À1 with an increase in the UV power dissipation from 5 W to 11 W.…”
Section: Effect Of Power Dissipationmentioning
confidence: 72%
See 4 more Smart Citations
“…Kinetic analysis revealed that for the change in power dissipation from 8 W to 32 W, the rate constant was found to increase from 0.010 min À1 to 0.018 min À1 . Pawar et al [19] reported a similar trend for the ultraviolet induced degradation of aqueous solution of polyvinyl pyrrolidone (PVP) investigated over the power dissipation range of 5 W to 11 W and it was established that the kinetic rate constant increased from 3.1 Â10 À2 min À1 to 7.3 Â 10 À2 min À1 with an increase in the UV power dissipation from 5 W to 11 W.…”
Section: Effect Of Power Dissipationmentioning
confidence: 72%
“…In addition, after the completion of initial laboratory scale optimization studies, scale up studies have been performed to check the effectiveness of the degradation approaches at large scale operation. The extent of degradation has been quantified in terms of the change in the intrinsic viscosity of the polymer solution, which is an easy method for monitoring the rate of degradation [8,9,19,24]. Further, Fouriertransform infrared (FTIR) spectra for untreated and treated guar gum solution were also analyzed to check the possible changes in the chemical structure.…”
Section: àmentioning
confidence: 99%
See 3 more Smart Citations